Implications of the Role Playing Learning Model in Developing Social Care Characters in Social Sciences Subjects for Class V Students of UPT SPF SDN Mangkura I Makassar City - Amriani, Amriani; Yunus, muh; Rahman, Nawir (CV. Rayyan Dwi Bharata, 2025)
This research aims to analyze the application of the role playing learning model in developing social care character in class V students at UPT SPF SDN Mangkura I Makassar City in social studies subjects. Using qualitative research methods, this research involved the Principal, Class Teacher, and 5 students. The research results show that the role playing learning model significantly improves students' social care character, increases their sensitivity to social issues, and encourages active participation in group activities that require cooperation and empathy. This model also makes it easier for students to understand abstract social concepts through direct practice in situations that are relevant to everyday life. The implications of this research emphasize the importance of implementing interactive and participatory learning methods in forming students' positive character.